Tuning the Interlayer Interactions of 2D Covalent Organic Frameworks Enables an Ultrastable Platform for Anhydrous Proton Transport - Jiang, Guoxing; Zou, Wenwu; Ou, Zhaoyuan; Zhang, Longhai; Zhang, Weifeng; Wang, Xiujun; Song, Huiyu; Cui, Zhiming; Liang, Zhenxing; Du, Li (Angewandte Chemie International Edition, 2022)
The development of effective, stable anhydrous proton‐conductive materials is vital but challenging. Covalent organic frameworks (COFs) are promising platforms for ion and molecule conduction owing to their pre‐designable structures and tailor‐made functionalities. However, their poor chemical stability is due to weak interlayer interactions and intrinsic reversibility of linkages. Herein, we present a strategy for enhancing the interlayer interactions of two‐dimensional COFs via importing planar, rigid triazine units into the center of C3‐symmetric monomers. The developed triazine‐core‐based COF (denoted as TPT‐COF) possesses a well‐defined crystalline structure, ordered nanochannels, and prominent porosity. The proton conductivity was ≈10 times those of non‐triazinyl COFs, even reaching up to 1.27×10−2 S cm−1 at 160 °C. Furthermore, the TPT‐COF exhibited structural ultrastability, making it an effective proton transport platform with remarkable conductivity and long‐term durability. An ultrastable and anhydrous covalent organic framework (COF)‐based proton conductor is prepared by tuning the interlayer interaction via importing planar and rigid triazine units into the center of C3‐symmetric monomers. This work provides a solution to the instability of imine‐linked COFs and contributes to the design and development of COF‐based energy‐related devices with proton‐transport systems.